2020
DOI: 10.34071/jmp.2020.6.2
|View full text |Cite
|
Sign up to set email alerts
|

The situation of antibiotic use for diarrhea treatment on pediatric inpatient at Pediatrics - Kien Giang General Hospital in 2019-2020

Abstract: Background: To survey for evaluation the use of antibiotic for diarrhea treatment on pediatric inpatient in compliance with MOH, WHO or treatment regimen. Objectives: (1) To describe the situation of antibiotic use for diarrhea treatment and (2) to determine factors that affected on indication of antibiotic for pediatric inpatient under 15 years at Kien Giang General Hospital in 2019. Subjects and methods: A cross-sectional study on 251 medical records of pediatric inpatients who treated by one of any drug fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…In our study, at the baseline the proportion of patients with fasting blood glucose levels reached 35.8%, similar to that of authors Dam Thi Huong Lien (32.4%) [3], higher than the study of author Le Van Mo (24%) [4]. From this, it can be seen that, although fasting glucose control is very important to limit complications, the target rate of achievement in type 2 diabetes patients has very low kidney damage.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In our study, at the baseline the proportion of patients with fasting blood glucose levels reached 35.8%, similar to that of authors Dam Thi Huong Lien (32.4%) [3], higher than the study of author Le Van Mo (24%) [4]. From this, it can be seen that, although fasting glucose control is very important to limit complications, the target rate of achievement in type 2 diabetes patients has very low kidney damage.…”
Section: Discussionsupporting
confidence: 87%
“…Research by Ahmed Medina et al kidney complications in type 2 diabetes patients found that the median duration of CKD is 5 years after diabetes detection, with an average annual incidence of 193/10,000 [8]. 76.4% of patients treated with Insuli alone, a ratio similar to Le Van Mo in 96 diabetic nephropathy patients in Kien Giang in 2021 (85%) [4].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation